Responding to Sexual Offending Perceptions, Risk Management and Public Protection - McCartan, K.; McCartan, K. (Palgrave Studies in Risk, Crime and Society, 2014)
This collection brings together international contributors from multiple disciplines to discuss the current public, social and governmental understandings and responses to sexual violence. Exploring issues such as how to manage sex offenders, the volume provides recommendations for how to reduce offending and improve community engagement.